2000
DOI: 10.1159/000028890
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida in Saudi Arabia: Is Consanguinity among the Parents a Risk Factor?

Abstract: Introduction: Spina bifida is an important birth defect. Its incidence differs from one country to another due to different factors. The aims of this study were: (1) to estimate the incidence of spina bifida in Al-Madinah Al-Munawarah and compare it with the Eastern part of the Kingdom, and (2) to find out if consanguinity is a risk factor. Methodology: A prospective study was conducted over the period from April 1996 to March 1997 in the city of Al-Madinah Al-Munawarah, Western Province, Saudi Arabia. New cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 7 publications
2
23
1
4
Order By: Relevance
“…Some researchers in the Eastern Mediterranean Region have reported that consanguinity in parents of babies with NTD is high [45,46]. The other significant difference between the cases and controls in the present study was the consumption of medications in the 1st trimester of pregnancy, a factor that is widely accepted as a cause in congenital malformations.…”
Section: Discussioncontrasting
confidence: 42%
“…Some researchers in the Eastern Mediterranean Region have reported that consanguinity in parents of babies with NTD is high [45,46]. The other significant difference between the cases and controls in the present study was the consumption of medications in the 1st trimester of pregnancy, a factor that is widely accepted as a cause in congenital malformations.…”
Section: Discussioncontrasting
confidence: 42%
“…It has shown that the rate of consanguineous marriage is high in NTD births (Murshid, 2000). In different Middle Eastern countries the rate of consanguineous marriages varies from 23.3% to 57.9% (Khoury & Massad, 1992;Teebi, 1994) The incidence of consanguineous marriage in Algeria was 23-34% (Benallegue & Kedji 1984;Zaoui & Biemont, 2002) and the frequency of consanguineous marriage rates were 40.5 and 30.6% in rural and urban settings, respectively (Zaoui & Biemont, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to confirm the suggestion that there is an increase risk for NTD in children born of consanguineous parents. The possibility that consanguinity could be a risk factor for NTD in a population requires further research (Murshid, 2000;Rajab et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Kulkarni reported the incidence of neural tube defects seen in 1.1%, higher incidence in CON families, 1.42% when they are 1 st cousins, 0.86% when they are far related, 0.57% in non-CON, 2.06% in uncle niece [31]. Consanguinity rates were noted to be higher among parents of newborns with congenital hydrocephalus and neural tube defects than in the general population [33,34].…”
Section: Infertilitymentioning
confidence: 99%